Fault Current of PV Inverters Under Grid-Connected Operation: A Review - Buzo, Ricardo Fonseca [UNESP]; Barradas, Henrique Molina [UNESP]; Leao, Fabio Bertequini [UNESP] (Springer, 2021)
As well as many benefits, many conflicts arise with the large-scale connection of distributed generation (DG) in distribution networks. Leading the protection devices to malfunction and increasing the complexity of fault location refer to the main DG impacts under fault condition. These issues are even more challenging by considering a scenario with photovoltaic (PV) distributed generation since there is an expressive number of articles presenting divergent claims about the fault current value reached by PV inverters. The different values reported in the literature increase the uncertainty about the real fault contribution from PV inverters. Under such a scenario, a wide survey and a critical review are presented in this article in order to show such divergence and to present a more intuitive insight into fault currents from PV inverters.
Keywords: Distribution network; Distributed generation; Photovoltaic inverter; Fault current contribution